2014
DOI: 10.1039/c4cc03417a
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence-dependent photoluminescence enhancement in a cationic conjugated polyelectrolyte

Abstract: DNA sequence-dependent photoluminescence enhancement is found for a cationic polyelectrolyte complexed with single stranded DNA and described as a result of an interplay between electrostatic attraction and the π-π stacking between the polyelectrolyte's backbone and DNA's bases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Beyond their biological purpose, chiral biomacromolecules, such as DNA, peptide, protein, and polysaccharide, have an interesting application as media for induce chirality in achiral PThs. [64][65][66][67][68] The control of helical superstructures can be achieved by mixing these chiral macromolecules with a previously synthesized achiral PThs, in which charged group are often incorporated into the PThs to afford electrostatic interactions with the biomacromolecules, and the specific right-handed or left-handed chirality is governed by topology of the chiral biomacromolecules. Surin's group made a systematic investigation of a variety of combinations of the charged PThs and DNAs.…”
Section: Chirality Induced By Biomacromoleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond their biological purpose, chiral biomacromolecules, such as DNA, peptide, protein, and polysaccharide, have an interesting application as media for induce chirality in achiral PThs. [64][65][66][67][68] The control of helical superstructures can be achieved by mixing these chiral macromolecules with a previously synthesized achiral PThs, in which charged group are often incorporated into the PThs to afford electrostatic interactions with the biomacromolecules, and the specific right-handed or left-handed chirality is governed by topology of the chiral biomacromolecules. Surin's group made a systematic investigation of a variety of combinations of the charged PThs and DNAs.…”
Section: Chirality Induced By Biomacromoleculesmentioning
confidence: 99%
“…The CD intensity of the ssDNA/41d complex decreased in order of homopyrimidine oligonucleotide (ODN)dT > homopurine ODNdA > mixed ODNdR 20 &dR rev20 , because the strong binding between F I G U R E 1 0 Structures of achiral polythiophenes (PThs) in which optical activity is induced by external chiral medium F I G U R E 1 1 CD spectra of (A) ssDNAd(T) 20 :41 and (B) xsDNAd(X) 20 :41d in a 1:1 molar ratio. Reproduced with permission from Liu et al 68 dA and cationic 41d significantly distorted the helix configuration. For dT, the CD intensity enhanced with the increased ODN sequence length.…”
Section: Chirality Induced By Biomacromoleculesmentioning
confidence: 99%
“…12,15,20,21 Recently, Leclerc et al pointed out that the fluorescence signal, and therefore the detection sensitivity of label-free DNA/CPT hybridization biosensors (i.e. 23 This is interpreted as a direct consequence of the different conformational changes and binding mechanisms of CPT with various DNA sequences, affecting the homogeneity of the assays. 22 For other single-stranded DNA/CPE complexes, it was also observed that the photoluminescence properties of CPEs depend on the DNA sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Side‐ or main‐chain polyelectrolytes that contain charged, π‐conjugated repeat units are an interesting class of materials for potential applications in chemo‐ or biosensing as well as optoelectronic devices such as solar cells or organic light emitting diodes . In recent years, side‐chain conjugated polyelectrolytes based on several backbone motifs were developed including polyfluorenes, fluorene–benzothiazole copolymers, polythiophenes, poly‐ p ‐phenylenevinylenes, poly‐ p ‐phenyleneethynylenes among others for applications in sensing, imaging, as well as for enzyme activity, and charge transport studies . Fully conjugated poly(pyridinium salt)s, or polyelectrolytes containing viologen, as well as diethynylpyridinium units as main‐chain polyelectrolytes have been synthesized mainly for biosensing and optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%